Karakteristik balita, ASI eksklusif, dan keberadaan perokok dengan kejadian stunting pada balita - Nurul Khairani; Santoso Ujang Effendi (AcTion: Aceh Nutrition Journal, 2022)
Stunting has an impact on cognitive function disorders, endurance, productivity, and potential to experience degenerative diseases. The aim of research was to measure the association between characteristics of children, exclusive breastfeeding, and presence of smokers with incidence of stunting. The design of research was a Cross Sectional. The sample was a toddler aged 12-59 months who visited to Integrated Healthcare Center (Posyandu) in Ratu Samban District, Bengkulu City in 2017. Samples were taken using Accidental Sampling technique as many as 102 toddlers. Data were collected by conducting interviews based on questionnaires, looking at maternal and child health books, and anthropometric measurements. Data analysis using Chi-Square test. The results, there was no significant correlation between characteristics of toddler (such as age (p= 0,175), gender (p= 0,439), birth weight (p= 0,218), birth length (p= 0,080)), exclusive breastfeeding (p= 0,362), and presence of smokers (p= 0,940) with incidence of stunting. In conclusion, there was no significant relationship between characteristics of toddlers, exclusive breastfeeding, and presence of smokers with incidence of stunting. It is recommended to Public Health Center to intervene in first thousand days of life in form of nutrition fulfillment, antenatal care, and education about the dangers of smoking for pregnant mother and toddler.